Covid-19 and Its Relationship to the Application of Distance Education in Teaching Social Studies Curriculum for the Upper Basic Stage from the Teachers’ Point of View - Alnwairan, Adnan Mohammad; Hassan, Salsabil Adeeb (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify Covid-19 and its relationship to the application of distance education in teaching social studies curriculum for the upper basic stage from the teachers’ point of view. The study has used the descriptive-analytical approach, where a questionnaire was employed as the study instrument. The population of the study consisted of a random sample from (311) Social studies teachers. The tool was distributed electronically through the use of social media and email to Social studies teachers of upper basic stage in public schools in three governorates, Amman, Salt and Irbid. The results showed that the impact of COVID-19 on teaching social studies curriculum for the upper basic stage was moderate. Furthermore, the level of applying distance education when teaching the social studies curriculum to the upper basic stage from the Teachers’ Point of view was moderate as well. The results also showed that there is a significant relation between COVID-19 and the level of distance education application when teaching the social studies curriculum for the upper basic stage. The current study recommends going beyond the schools’ scope and researches higher education from across the entire Hashemite Kingdom of Jordan as a follow-up to this research’s findings. Further qualitative research would be needed in the future to accurately assert the level of applying distance education.